Биоморфологические особенности семян и семенная продуктивность некоторых видов рода Dianthus L. в Донбассе - Усманова, Н.В. (Промышленная ботаника, 2003)
The biomorphologic features of the seeds and seed productivity of 11 Dianthus species: D. anatolicus Boiss., D. carmelitarum Reut. ex Borb., D. cruentus Griseb., D. gratianopolitanus Vill., D. lumnitzeri Wiesb., D. microlepis Boiss., D. simonkaianus Jav., D. spiculifolius Schur., D. tianschanicus Schischk., D. turkestanicus Preobr. D. zonatus Fenzl. were studied. It was found that the species under investigation, with the exception of D. spiculifolius, have a high seed production and the viability of seeds. It testifies to a sufficient degree of adaptation of these species to the conditions of Donbass.